Identification for gain-scheduling: a balanced subspace approach - Lovera, M.; Mercere, G. (2007 American Control Conference, 2007)
The problem of deriving MIMO parameter- dependent models for gain-scheduling control design from data generated by local identification experiments is considered and a numerically sound approach is proposed, based on subspace identification ideas combined with the use of suitable properties of balanced state space realisations. Simulation examples are used to demonstrate the performance of the proposed approach.